HUBUNGAN ANTARA KESEIMBANGAN TUBUH DAN KOGNISI TERHADAP RISIKO JATUH LANJUT USIA DI PANTI WREDA PUCANG GADING - ROSDIANA, Ika; Cahyani LESTARI, Aghnia (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2020)
The aging process is marked by the degeneration of organ systems and tissues, physiological changes occur that cause the elderly to experience impaired mobilization due to reduced muscle strength. Another thing is the emergence of cognitive dysfunction can be experienced by patients who progress to dementia, both of which can increase the risk of the elderly experiencing impaired balance and risk of falling. This study aims to find a correlation between body balance and cognition with the risk of falling in the elderly carried out at the Pucang Gading Nursing Home in Pedurungan District, Semarang. In this type of observational analytic study with a cross-sectional design, the independent variable is balance and cognition while the dependent variable is the risk of falling. The results showed the highest body balance level in the medium category was 66.0%, the high was 21.3% and the low was 12.8%. For the category of cognitive function in the elderly, it is found that definite respondents are 8.5%, probable 25.5%, and normal 66.0% respondents. The risk of falling in the elderly is low at 63.8%, while the risk of falling at a moderate level of 19.1% and high at 17.0%. . Spearman correlation test results between balance and risk of falling p = 0.000 (p <0.05) with a value of r = -0.497 while the spearmen correlation test between cognition and risk of falling obtained p = 0.224 (p <0.05). In conclusion, there is a relationship between balance and risk of falling with a value of p = 0,000 with a value of r = -0.49 and there is no relationship between cognition with a risk of falling p = 0.224.